IDENTIFYING AND OVERCOMING SOME FATIGUE-CAUSING FACTORS EXISTING IN ONLINE READING CLASS OF AMIKOM PURWOKERTO PSDKU YOGYAKARTA DURING COVID-19 QUARANTINE - Anita Wijayanti; Yeremia Andi Irawan; Yohanes Bambang Gunawan (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract COVID-19 forced AMIKOM Purwokerto to convert its traditional classes to online learning. During this online learning, problems have started to unravel, and one of them is fatigue, which was confirmatively experienced by 55% students of Reading IV. This study, utilizing a quantitative research method, intended to find the causes of the fatigue and design practicable solutions. Through observations, group interview, and literature reviews, some main factors that caused fatigue were revealed: Zoom fatigue; tasks which were too difficult and numerous; presentation of materials which did not properly comply with the students’ online conditions and unfamiliarity to Google Classroom; eye fatigue (digital eye strain), bad postures during learning, lockdown fatigue, and frustration over signal and internet problems. To overcome the fatigue, the researchers reduced the time for video conferences and created asynchronous short videos for learning, selectively adjusted tasks in terms of number and difficulty, simplified presentations of materials and helped the students to become more familiar with Google Classroom, and addressed the problems from eye strain, bad postures, and lockdown fatigue in the reading materials so the students could solve those problems based on the texts given or find a more viable solution. Those solutions reduced the number of drained students to only 25% and in addition 60% students claimed that the modifications brought a positive impact on their learning. Keywords: fatigue, distance learning, COVID-19, Zoom fatigue